PENGARUH BUDAYA KAIZEN, FAKTOR PERSONAL DAN FAKTOR ORGANIZATIONAL TERHADAP PRODUKTIVITAS PEGAWAI PADA KANTOR BUPATI PIDIE - Cut Italina; Nanda Yani (Jurnal Sains Riset, 2022)
This study aims to examine the influence of kaizen culture, personal factors and organizational factors on employee productivity at the Pidie Regent's Office. The number of samples used as many as 70 respondents with a total population of 139 employees. The data were analyzed using SPSS version 20. Previously, it was done before the Multiple Linear Regression Analysis was carried out to test the validity and reliability of the data. Furthermore, the Classical Assumption test which includes normality, heteroscedasticity and multicolonearity tests. From the results of the study, it can be concluded that the regression formulation is as follows Y=1.388+0.404 X1+ 0.203 X2 + 0.330 X3 The results of research on the influence of kaizen culture obtained a tcount value of 4.066 which is greater than ttable 1.998 with a probability of 0.000 smaller than 0.05, it can be interpreted that the kaizen culture has a partial and significant influence on the work productivity of employees at the Pidie Regent's office. Furthermore, the results of research on the influence of personal factors obtained a tcount value of 2,050 which is greater than ttable 1,998 with a probability of 0.04 less than 0.05, it can be interpreted that personal factors have a partial and significant influence on work productivity at the Pidie Regent's Office. The results of the study on the influence of organizational factors obtained that the tcount value of 3.297 is greater than ttable of 1998 with a probability of 0.002 less than 0.05, it can be interpreted that organizational factors have a partial and significant influence on work productivity at the Pidie Regent's Office.Keywords: Kaizen Culture, Personal Factors, Organizational Factors and Productivity